Sheikh Mujib in parliament, 1955-58 - Mujibur Rahman, Sheikh, 1920-1975.; Rahman, Ziaur, 1940- (Dhaka : Agamee Prakashani, 2016)
On various political issues of Pakistan, including Bangladesh former East Pakistan.
"Collection of speeches delivered by Bangabandhu Sheikh Mujibur Rahman in the Constituent Assembly and National Assembly of Pakistan between 1955 and 1958"--T.p. verso.
Includes index.
AAL
Keywords: Pakistan -- Politics and government; Bangladesh -- Politics and government